Not so Simple: Examining the Gendered Nature of Intimate Partner Assault Victimizations - Chamberlain, Alyssa W. (Journal of interpersonal violence, 2025)
Although prior research has established a relationship between neighborhood structure and intimate partner violence (IPV), much of this literature focuses on serious IPV, despite the fact that less serious forms of IPV comprise the majority of IPV instances. Further, women are far more likely to experience all types of IPV victimization relative to men, especially simple assault, yet the relative importance of neighborhood structure across gradations of IPV and victim sex is relatively unexplored. We use data from Los Angeles, CA, and disaggregate IPV assaults across victim sex to examine whether neighborhood factors have differential effects on simple and aggravated IPV. We find differential effects of neighborhood structure by victim sex, especially for simple assault. Most notably, we find that neighborhood racial composition has significantly greater effects on females relative to male victims of simple IPV assault, while residential stability is protective of women more so than men. Only the percent of vacant or owner-occupied housing was specific to male simple IPV victimization. This suggests that neighborhood-based interventions should differ depending on the type of IPV being targeted.